Reticulocyte count in red-blood-cell units stored in AS-1 (2013)
Background and objectives: Previous data that showed maintenance of reticulocyte percentage in whole blood stored in CPDA-1 have led to the assumption that reticulocyte maturation becomes arrested during refrigerated storage. However, reticulocyte behaviour in red-blood-cell units stored in additive solutions has not yet been studied. This study was thus aimed at determining reticulocyte count and reticulocyte subtypes in red-blood-cells units stored in AS-1. Materials and methods: Reticulocyte percentage and subtypes were determined by flow cytometry with thiazole orange in six red-blood-cells units stored in AS-1. Results: Reticulocyte count was 26·8 ± 4·6 × 109/l at week 0·5 and 8·2 ±2·9 × 109/l at week 6. Total haemolysis during storage was 0·19 ± 0·08%. High-fluorescence reticulocytes were 2·0 ± 3·2 × 109/l at week 0·5 and decreased by weeks 2, 4 and 6. Low-fluorescence reticulocytes were 22·1 ± 3·1 × 109/l at week 0·5 and decreased by weeks 4 and 6. Conclusion: A significant decrease in reticulocytes occurred during red-blood-cells units' storage in AS-1. Even if it were assumed that all of haemolysed cells during storage were reticulocytes, there are a number of them whose disappearance cannot be explained by this mechanism. Changes observed in reticulocyte subtypes suggest that they mature during storage. © 2013 International Society of Blood Transfusion.